Engineering light-driven biomineralization for a sustainable carbonate economy - Falkenroth, Michaela; Dann, Marcel (Frontiers in Photobiology, 2025)
Photosynthetic activity of cyanobacteria is a prominent driver of cell-surface catalysed extracellular calcium carbonate (CaCO3) precipitation. This natural process termed “biomineralization” occurs only under specific circumstances but has given rise to significant carbonate rock formation throughout geological time. Engineering cyanobacterial cell surfaces for enhanced and constitutive biomineralization of abundant ocean-water dissolved Ca2+ and flue-gas CO2 into CaCO3 may allow for the biotechnological re-capture of CO2 released by industrial processes such as thermal decarboxylation of CaCO3. This may both limit net greenhouse gas emissions and transform CaCO3 into a sustainable resource. Drawing from geological precedent and basic biological research, this perspective outlines promising synthetic biology strategies to convert cyanobacterial biomineralization into a cornerstone technology for a sustainable carbonate economy.